1993
DOI: 10.1121/1.405402
|View full text |Cite
|
Sign up to set email alerts
|

Rate of loudness growth for pure tones in normal and impaired hearing

Abstract: The present article provides an analysis of loudness growth rates in normal and cochlear-impaired hearing for diverse groups with respect to age and backgrounds. Slopes are obtained from absolute magnitude estimation and magnitude production of loudness (measured values), and from cross-modality matching and absolute magnitude estimation of apparent length (predicted values). Consistent with an earlier study [R. P. Hellman and C. H. Meiselman, J. Acoust Soc. Am. 88, 2596-2606 (1990)], slopes calculated within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
26
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 28 publications
9
26
0
2
Order By: Relevance
“…1). This supports the consideration of at least two different existing models of loudness growth (softness imperception and recruitment) and is in qualitative agreement with the observation that the standard deviation of estimated slopes of the loudness growth function for a group of people increase as a function of the average hearing threshold of the group (Hellman and Meiselman, 1992). From a more practical point of view, this variability underscores the general idea that simply knowing a listener's threshold is not sufficient to determine the person's perception of loudness as a function of stimulus level.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…1). This supports the consideration of at least two different existing models of loudness growth (softness imperception and recruitment) and is in qualitative agreement with the observation that the standard deviation of estimated slopes of the loudness growth function for a group of people increase as a function of the average hearing threshold of the group (Hellman and Meiselman, 1992). From a more practical point of view, this variability underscores the general idea that simply knowing a listener's threshold is not sufficient to determine the person's perception of loudness as a function of stimulus level.…”
Section: Discussionsupporting
confidence: 68%
“…Given the wide range of types of loudness growth observed in individual HILs (Hellman and Meiselman, 1992), and that the type of loudness growth cannot be determined by thresholds and discomfort levels alone, there is interest in advanced procedures that could be used to estimate loudness growth for fully customized non-linear hearing-aid fitting. Furthermore, an objective procedure for estimating loudness growth could be a valuable tool in providing customizable hearing-aid fitting for those not capable of performing standard psychoacoustical tasks (such as in infants or cognitively impaired adults).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the impaired listeners were divided into five groups based on the overall configurations of their hearing losses as indicated by the listener IDs shown in the first column. ͑A sixth group of normal controls is shown at the bottom.͒ If the hearing loss increased more than 50 dB over any octave, it was characterized as an abrupt loss ͑listeners A1 and A2͒; such a steep loss is likely to indicate that inner-hair cells are missing or nonfunctional in some frequency region starting at the beginning of the slope ͑Hell-man and Meiselman, 1993;Florentine et al, 1997͒. If the hearing loss was not abrupt and decreased 15 dB or more over any two-octave interval, it was characterized as a rising loss ͑R1 to R3͒.…”
Section: Listenersmentioning
confidence: 99%
“…Whereas considerable knowledge exists about the loudness of long-duration sounds in impaired listeners ͑for review, see Hellman and Meiselman, 1993;Moore, 1995;Moore and Glasberg, 1997͒, little is known about the loudness of brief sounds. Because most natural sounds are not steady state, but have amplitude peaks that typically are much shorter than the 50-150-ms integration time generally assumed for loudness ͑for review, see Scharf, 1978͒, knowledge of the loudness functions for brief sounds may be important for hearing-aid fitting and for general understanding of impaired listeners' auditory perception.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Heinz et al (2005) and Cai et al (2009) have suggested that changes occur in the auditory system beyond its periphery and that these more central changes are responsible for loudness recruitment. Regardless of its source, loudness recruitment can be examined through measures of loudness (Allen et al, 1990;Hellman and Meiselman, 1993;Buss et al, 1998). Hearing aids can be used to compensate for elevated thresholds, while also compressing the normal range of levels into the reduced dynamic range of patients with hearing loss.…”
Section: Introductionmentioning
confidence: 99%